The Reality and Requirements of the local standing Development in the Elshati region - Uonis Imbyah Abukhtowah, Mahmud Hamelah, Mohamed Shibah (Journal of Pure & Applied Sciences, 2019)
The main objective of this paper is to identify the realities and possibilities of sustainable local development in its three dimensions: the environmental dimension - the economic dimension - the social dimension (the dependent variable) in the Wadi Al Shati area and the main demographic factors affecting income - number of family members - place of residence - educational level (variables) The study followed the descriptive analytical methodology using the questionnaire tool. A simple random sample was selected from the villages, and a simple random sample from the city. The questionnaire was distributed to the villages of Wadi Al Shati (Al-Qarda and Adri) with 109 newspapers. Another questionnaire was distributed to the city of Brak (Municipality of Brak) by 43 questionnaires. The normal distribution of the sample from thirty items and more was taken into consideration and the SPSS package was used. Income in the city on the economic dimension of sustainable local development. The lack of justice in the distribution of public services between villages and the city. In agricultural land, which threatens the future of the agricultural sector as an important and major economic resource in the region.